Gestão ambiental: um estudo sobre a percepção do problema da desertificação no Estado do Rio Grande do Norte - Dantas, Carlos César Gadelha (2006)
The objective of this study was to investigate the environmental perception of: People with common-sense knowledge on the desertification process in RN. People with scientific knowledge on the desertification process in RN. Focal points in the combat at desertification of the RN and public ministery representant with actions in interinstitutional articulations promoter (and/or relative actions) at the desertification process in the RN. The research was carried in the city of Natal-RN and in two small cities of the Seridó region (RN): Caicó and Currais Novos. The research carried, is classified as exploratory and 22 people were interviewed. The research includes: The propension/intensity of the desertification in the RN and in the Seridó region; Evaluation of the knowledge of those interviewed, concerning the subject desertification ; Problems in order to combat desertification; Causes of desertification; The profile of the interviewed. The results of this present study indicate that the a desertification process is more agressive in the Seridó region than in the state of RN, being the two following: the absence of preocupation of the affected population with the process and the escarcity of governamental recurses, indicates how problems greather in the combat to the phenomen. Decreasing of produtivity in the agriculture and increasing of the migration to the urbans centers have been the main consequences of the process, that have at water scarcity, deforestation and extraction of argil (being this, regional factor), relevant variables in the influence to the surgiment of the desertification process of the RN